Politics, identity, and Mexico's indigenous rights movements - Eisenstadt, Todd A. (Cambridge (UK) : Cambridge University Press, 2011)
"Drawing on an original survey of more than 5,000 respondents, this book argues that, contrary to claims by the 1994 Zapatista insurgency, indigenous and non-indigenous respondents in southern Mexico have been united by socioeconomic conditions and land tenure institutions as well as by ethnic identity. It concludes that--contrary to many analyses of Chiapas's 1994 indigenous rebellion--external influences can trump ideology in framing social movements. Rural Chiapas's prevalent communitarian attitudes resulted partly from external land tenure institutions, rather than from indigenous identities alone. The book further points to recent indigenous rights movements in neighboring Oaxaca, Mexico, as examples of bottom-up multicultural institutions that might be emulated in Mexico and elsewhere in Latin America"--Provided by publisher.
Surveying the silence : traditional societies, indigenous rights, and the state in southern Mexico -- A tale of two movements : comparing mobilizations in Chiapas 1994 and Oaxaca 2006 -- Individual and communitarian identities in indigenous southern Mexico : a theoretical and statistical framework -- Agrarian conflict, armed rebellion, and the struggle for rights in Chiapas' Lacandon jungle -- Customary practices, women's rights, and multicultural elections in Oaxaca -- From balaclavas to baseball caps : the many hats of "real world" indigenous identities -- Reconciling individual rights, communal rights, and autonomy institutions : lessons from Chiapas and Oaxaca.
Originally published: 2010.
Keywords: Indians of Mexico -- Ethnic identity; Indians of Mexico -- Politics and government; Land tenure -- Social aspects -- Mexico; Indians of Mexico -- Ethnic identity; Indians of Mexico -- Politics and government; Land tenure -- Social aspects; Mexico